Cultural adaptations and cultural factors in EBI implementation with Latinx communities - Castro, Felipe González; Berkel, Cady; Epstein, Dana R. (Frontiers in Public Health, 2023)
This paper summarizes the history of cultural factors as significant constructs in the Latinx social and behavioral sciences literature. Cultural factors are constructs that capture important life experiences of Latinx individuals, families, and communities. Despite their importance for Latinx communities, Latinx cultural factors have not been fully incorporated into the literature of many social and behavioral science and health service areas, including prevention science and implementation science. This significant gap has limited the depth of assessment and a more complete understanding of the cultural life experiences of diverse Latinx community residents. Addressing this gap can increase this understanding and inform the design, dissemination, adoption, implementation, adaptation, and sustainability of evidence-based interventions (EBIs) developed to serve Latinx and other ethnocultural groups. Using NVivo 12, we conducted a thematic analysis of empirically-identified cultural factors in the area of Latinx/Hispanic stress-coping-outcomes research from the years 2000 to 2020. We conducted this thematic analysis from the Discussion sections of 60 empirical articles included in our prior systematic review of that literature. From this thematic analysis we interpret salient empirically-identified cultural factors, and offer future directions for the application of cultural factors in implementation science research and practice.